Development of microsatellite markers and detection of genetic variation between Goniozus wasp populations - Khidr, Sahand K.; Hardy, Ian C.W.; Zaviezo, Tania; Mayes, Sean (Oxford University Press, 2014)
Molecular genetic markers reveal differences between genotypes according to the presence of alleles (the same or different) at target loci. Microsatellite markers are especially useful codominant markers that have been used in a wide range of studies to elucidate the population structure and dynamics of a range of organisms, including agriculturally beneficial insects such as parasitic wasps (parasitoids). In the present study, twelve primer pairs were designed for the south Asian , Goniozus nephantidis (Muesebeck) (Hymenoptera: Bethylidae), and 24 for its New World congener, Goniozus legneri Gordh, parasitoids of the larvae of the lepidopteran coconut pest Opisina arenosella Walker (Lepidoptera: Crytophasidae) and other lepidopteran pests, respectively, in order to investigate polymorphism within and between populations. The wasps fingerprinted were a total of 85 G. nephantidis and G. legneri, including individuals belonging to three putatively different strains of G. legneri. Annealing gradient tests (50–65°C) were conducted to study the quality of the PCR amplification across an annealing temperature gradient using a mixed genotype DNA template from each species separately. Seven primer pairs, which amplified clear products of approximately the expected size of G. nephantidis and 18 of G. legneri, were then selected for capillary analysis for fragment size determination on a Beckmann CEQ 8000. Neither G. nephantidis nor G. legneri were polymorphic within populations. However, there were six primer pairs that did show polymorphism between G. legneri populations that originated from different geographical areas within South America (Uruguay and Chile). Furthermore, one primer pair revealed diversity between the two strains collected within Chile. One of the markers was subsequently used to provide unbiased assessment of primary sex ratio in G. legneri.